‘CIP BRS Nuti’: A New Orange Flesh Sweetpotato Cultivar - Mello, A.F.S.; Olegário Da Silva, G.; Silva, J. da; Samborski, T.; Ferreira, J.C.; Carvalho, J.L.V. de; Nuti, M.R.; Siquieroli, A.C.S.; Braga, M.B.; Díaz, F.; Grüneberg, W.J. (American Society for Horticultural Science, 2022)
The number of registered sweetpotato cultivars in Brazil is limited and they are mostly white-fleshed cultivars (Ministry of Agriculture, Livestock and Food Supply, 2021). ‘CIP BRS Nuti’ (CIP 106902.1) sweetpotato (Ipomoea batatas) was developed by the International Potato Center (CIP) in Peru by controlled crossing between the elite orange flesh sweetpotato (OFSP) clone (CIP101048.1) and the advanced OFSP clone (CIP194583.2). This clone will be released by Embrapa as a cultivar for Brazil, after being selected from among 80 clones imported from CIP. ‘CIP BRS Nuti’ is an OFSP with a mean commercial root yield of 35 t⋅ha−1 across 12 Brazilian site locations. The new cultivar presents resistance to Meloidogyne incognita, Meloidogyne javanica and Meloidogyne enterolobii root knot nematodes and a vigorous foliage that enables rapid establishment of the crop in comparison with the Beauregard cultivar (Rolston et al., 1987), which is the most cultivated OFSP in Brazil.